The rating of perceived exertion predicts intermittent vertical jump demand and performance - Pereira, Gleber; Correia, Ricardo [UNESP]; Ugrinowitsch, Carlos; Nakamura, Fabio; Rodacki, Andre; Fowler, Neil; Kokubun, Eduardo [UNESP] (Taylor & Francis Ltd, 2011)
The aims of this study were (a) to assess the ability of the rating of perceived exertion (RPE) to predict performance (i.e. number of vertical jumps performed to a fixed jump height) of an intermittent vertical jump exercise, and (b) to determine the ability of RPE to describe the physiological demand of such exercise. Eight healthy men performed intermittent vertical jumps with rest periods of 4, 5, and 6s until fatigue. Heart rate and RPE were recorded every five jumps throughout the sessions. The number of vertical jumps performed was also recorded. Random coefficient growth curve analysis identified relationships between the number of vertical jumps and both RPE and heart rate for which there were similar slopes. In addition, there were no differences between individual slopes and the mean slope for either RPE or heart rate. Moreover, RPE and number of jumps were highly correlated throughout all sessions (r=0.97-0.99; P0.001), as were RPE and heart rate (r=0.93-0.97; P0.001). The findings suggest that RPE can both predict the performance of intermittent vertical jump exercise and describe the physiological demands of such exercise.
Keywords: Countermovement jump; blood lactate concentration; heart rate; fatigue; rest period